Reframing Employee Engagement in the Digital Era: A Multilevel Review of Its Impact on Organizational Effectiveness - Wang, Yajuan; Balakrishnan, Parasuraman (INTI International University, 2025)
Employee engagement plays a vital role in enhancing organizational effectiveness, yet existing research lacks a unified framework that integrates its multilevel effects, especially under the influence of digital transformation. Fragmented theories and evolving work environments make it difficult to understand how engagement operates across individual, team, and organizational levels. This paper reviews and integrates four key theoretical perspectives—Kahn’s Psychological Conditions Theory, Self-Determination Theory, Social Exchange Theory, and Conservation of Resources Theory—to construct a multilevel model of employee engagement. It further explores how digital technologies reshape engagement through platform tools, algorithmic control, and virtual collaboration. Findings reveal that employee engagement contributes to performance, innovation, and strategic alignment, but digital transformation also introduces risks such as surveillance and emotional fatigue. The review highlights key research gaps, including the need for integrated multilevel models and context-specific digital engagement studies. This study contributes a novel conceptual framework that connects engagement theory with digital-era challenges, offering insights for future research and practical applications in human resource and organizational development.